(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
Educational games in preschool educational organizations and their importance. Educational games, as educational games, are among the games that correspond to the age characteristics of children. An important feature of didactic games is the presence of rules in them. In the game, there is an integral connection between the goal of the game, the rules of the game, and the actions of the game. The goal of the game determines the nature of the actions of the game. The rules of the game help to solve the game actions, the task and carry out the actions in the game. Through educational games, children are given new knowledge and concepts. In these games, the child’s comprehensive development, cognitive process, sensory culture, speech activity, and mental abilities are improved. Observing and following the rules of the game enriches the content of the game. Natural objects and objects are widely used in educational games. Time and space should be allocated in the child’s daily routine for educational games. Such games are held in groups or individually during training and outside of the game. In this case, the content and result of the game are carefully determined